1939
DOI: 10.1084/jem.70.5.443
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive Iron and Its Excretion in Urine, Bile, and Feces

Abstract: Recent experiments (3) in this laboratory gave clear evidence that the plethoric dog with all its iron stores well filled did not absorb radio-iron, in contrast to the anemic dog which took up such iron promptly and in considerable amounts from the intestinal tract. The transfer of the radioiron to new red blood cells in anemia is very rapid.The experiments tabulated below deal with excretion of radioactive iron after its intravenous injection as ferrous gluconate. It is generally accepted that the urine is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

1940
1940
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(19 citation statements)
references
References 7 publications
1
17
0
1
Order By: Relevance
“…Cumulative urine collections in three subjects contained less than 1 per cent of the administered dose. This confirmed in humans the previous ohservations in animals that significant quantities of radioactive iron are not excreted in the urine (13,14 …”
Section: Resultssupporting
confidence: 81%
“…Cumulative urine collections in three subjects contained less than 1 per cent of the administered dose. This confirmed in humans the previous ohservations in animals that significant quantities of radioactive iron are not excreted in the urine (13,14 …”
Section: Resultssupporting
confidence: 81%
“…With further reference to the fate of plasma iron diverted in the presence of inflammation, it may be pointed out that Hahn et al (12) showed that the urine and bile contain negligible quantities of iron injected intravenously in doses even larger than those used in the present study. In balance studies, Schaefer (13) found no evidence of increased excretion of iron in children with infection.…”
Section: Discussionmentioning
confidence: 65%
“…Iron loss arises from epithelial cell sloughing and minor bleeding and totals less than 2 mg per day on average (8). Because regulated iron excretion systems do not exist in humans, total body iron homeostasis is regulated at the level of dietary absorption (9,10). Dietary nonheme iron is ferric and must be reduced to the ferrous state for membrane transport.…”
Section: Iron Homeostasis In Humansmentioning
confidence: 99%